2017
DOI: 10.1016/j.ymgme.2017.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Beyond mRNA: The role of non-coding RNAs in normal and aberrant hematopoiesis

Abstract: The role of non-coding Ribonucleic Acids (ncRNAs) in biology is currently an area of intense focus. Hematopoiesis requires rapidly changing regulatory molecules to guide appropriate differentiation and ncRNA are well suited for this. It is not surprising that virtually all aspects of hematopoiesis have roles for ncRNAs assigned to them and doubtlessly much more await characterization. Stem cell maintenance, lymphoid, myeloid and erythroid differentiation are all regulated by various ncRNAs, including microRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 135 publications
(167 reference statements)
0
12
0
Order By: Relevance
“…lncRNAs are a type of ncRNAs that are more than 200 bps in length (Wilkes et al, 2017). LncRNAs were observed to be dysregulated in multiple human diseases, such as diabetes, cardiovascular diseases and cancers (Yang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…lncRNAs are a type of ncRNAs that are more than 200 bps in length (Wilkes et al, 2017). LncRNAs were observed to be dysregulated in multiple human diseases, such as diabetes, cardiovascular diseases and cancers (Yang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…More recent researches indicate that due to their extended lengths, lncRNAs could regulate protein expression by binding and sequestering their mRNAs. That is why some lncRNAs are also known as miRNA sponges 24 . It has been suggested that both miRNAs and lncRNAs are involved in the regulation of myeloid cell lifespan 14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…Data indicate that miRNAs are expressed in a temporally and spatially controlled manner within the brain and are also well‐known contributors to synaptic plasticity, neuronal differentiation, and development . MicroRNAs also play a major role in immune functioning, hematopoiesis, proliferation, neurodegenerative disorders, embryonic development, and in‐born errors of metabolism . miRNAs have been utilized as therapeutic targets, as they are reported to act as biomarkers for several diseases .…”
Section: Types Of Ncrnasmentioning
confidence: 99%